1955
DOI: 10.1099/00221287-12-3-484
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Bacteriophage on Streptococcus pyogenes

Abstract: SUMMARY: By the selective action of certain bacteriophages on cultures of susceptible streptococci it is possible to alter or enhance certain of their characteristics. The extractable M antigen may be greatly increased ; non-mucoid strains may become completely mucoid with or without the increase in M antigen. Some phageselected cultures have shown a marked increase in mouse virulence and some an ability to survive in normal human blood not possessed by the parent strain.Despite the great amount of work publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1957
1957
1998
1998

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…This agent is capable of lysing live or chloroform-killed suspensions of streptococci of groups A, C and E, and it seems likely that the agent is responsible for the nascent lysis observed by Evans on streptococci belonging to these groups. Virulent phages active against group A streptococci and used in previous work (Maxted, 1955) also gave nascent lysis of otherwise resistant members of group A; such phage propagations also yielded a lytic principle similar to the one described here, although so far they have always been much less potent. This would agree with the observations of Evans that phage B563 was by far the most active of her phages in respect of nascent lysis.…”
Section: Discussionmentioning
confidence: 85%
“…This agent is capable of lysing live or chloroform-killed suspensions of streptococci of groups A, C and E, and it seems likely that the agent is responsible for the nascent lysis observed by Evans on streptococci belonging to these groups. Virulent phages active against group A streptococci and used in previous work (Maxted, 1955) also gave nascent lysis of otherwise resistant members of group A; such phage propagations also yielded a lytic principle similar to the one described here, although so far they have always been much less potent. This would agree with the observations of Evans that phage B563 was by far the most active of her phages in respect of nascent lysis.…”
Section: Discussionmentioning
confidence: 85%
“…Since many of the group A streptococcal tance does not develop uniformly in all microbial species. Conbacteriophages were isolated originally from sewage [25,26], tinued susceptibility of Treponema pallidum to penicillin the recent observation of penicillin-resistant enterococci raises indicates that resistance may not invariably occur despite powthe question of whether these organisms might provide the erful selective pressures that would favor its emergence. There vehicle by which phage transfer of penicillin resistance to group is, however, a time factor to be considered.…”
Section: Historically Examples Of the Introduction Of Toxins Under Ge-mentioning
confidence: 99%
“…Some of these differences reported by various authors may be attributable to the use of living or heat-killed cells, to the media employed, to differences in the smoothness of M + and M-lawns, to use of paired and unpaired variants, or to other variables. Our findings and those of Maxted (1955) suggest that continued exposure of viable streptococci to relatively large amounts of trypsin may be an important factor for optimal demonstration of differences between M + and M -variants, as trypsin-treated living cells may rapidly regenerate M protein (Fox and Krampitz, 1956). …”
Section: Discussionmentioning
confidence: 73%
“…On the other hand, Cleary and Johnson (1977) showed that heat-killed cells of mutants producing large amounts of M protein adsorbed phage poorly, a finding that was reversed by trypsin treatment. In studies of a pair of M + and Mvariants (Maxted, 1955) lawns of M +variants were more resistant to phage infection than lawns of the M -variants. When Maxted grew these variants in broth containing trypsin and repeated the phage titration on trypsin-containing plates, he found no difference in the titres obtained with the M + and the M -variants.…”
Section: Discussionmentioning
confidence: 94%